Tau-Tau in the narrative of spatial awareness of the Toraja community: A sociological review - Ahmadin, Mr.; Usman, Sahrah Fadillah (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
This study aims to analyze the symbolic meaning of Tau-Tau (wooden statues depicting the deceased) in the narrative of spatial awareness among the Toraja people. Using a sociological approach, this study explores the existence of Tau-tau, which not only serves as a physical representation of the deceased, but also acts as a symbolic marker that actively shapes the collective understanding of space. In this context, the spaces referred to are sacred spaces (the spirit world), social spaces (settlements and ceremonial sites), and cosmological spaces. The research method used is qualitative, with data collection techniques involving participant observation and in-depth interviews with traditional elders, families who own Tau-Tau, and the general public in Tana Toraja. The results of the study reveal that the presence of Tau-Tau on the cliffs of burial grounds in the hills creates a cultural landscape that connects the world of the living with the world of the ancestors. Tau-tau become silent but powerful narrators that affirm social hierarchy, family status, and the continuity of the relationship between the living and the dead. In the context of Toraja community spatial awareness, this is a complex socio-cultural construction, in which tau-tau function as key elements in interpreting, regulating, and animating that space. The main contribution of this research is to provide a deeper understanding of the socio-cultural dynamics of local communities, particularly regarding the interrelationship between symbols, space, and social structures